Lifelong Learning Supported by Artificial Intelligence and Technology for Sustainable Development Goals: An OECD Perspective - Akpinar, Burhan; Barut, Muzeyyen; Akpinar, Esra Nur; Balikci, Hasan Celal (Wiley, 2025)
This study aims to examine the role of lifelong learning in achieving the sustainable development goals (SDGs) and the impact of artificial intelligence and technology in this role for OECD countries in 2005-2019. The study method, Method of Moments Quantile Regression (MMQREG), is powerful and up-to-date. To test the robustness of the findings obtained in the MMQREG method, the Kernel regularized least squares (KRLS) method, an estimator based on machine learning, and the Driscoll-Kraay estimator, which can make consistent estimates in the presence of endogeneity and autocorrelation, were preferred. As a result of the analyses, lifelong learning is effective in achieving the SDGs, and artificial intelligence and technology strengthen the impact of lifelong learning in achieving the SDGs. In addition, artificial intelligence, technology, and human capital improve the SDGs, while population density weakens the SDGs. The findings take into account the impact of lifelong learning in achieving the SDGs and can guide policy makers.
Keywords: artificial intelligence; lifelong learning; SDG; technology